Letter to the Editor on the article "Clinical evaluation of balloon occlusion of the lower abdominal aorta in patients with placenta previa and previous cesarean section: A retrospective study on 43 cases.": The drier the surgical field, the better?. (March 2017) - Matsubara, Shigeki; Takahashi, Hironori; Baba, Yosuke; Nakamura, Hiroyasu
Highlights: Aortic balloon occlusion can reduce bleeding during abnormally-invasive-placenta surgery, but depending on the situation. Preset occlusion can be performed to all suspicious of abnormal placentation, or based on the intra-operative findings. Discussion should be made regarding which type of preset balloon occlusion is better. Aortic balloon occlusion can be associated with serious adverse events, and, thus, patient selection is mandatory.